Assessing the effects of seasonal grazing on holm oak regeneration: Implications for the conservation of Mediterranean dehesas - Carmona, Carlos P.; Azcárate, Francisco M.; Oteros-Rozas, Elisa; González, José A.; Peco, Begoña (Biological Conservation, 2013)
Scattered trees in agricultural landscapes are globally declining due to the intensification of agricultural practices. Dehesas, highly species-diverse Mediterranean open woodlands, are seriously affected by this decline, because of a generalized regeneration failure of oak, which compromise their long-term stability. Traditionally, dehesas were the wintering areas for transhumant herds, but transhumance is disappearing in the Mediterranean, due to multiple causes. Reductions in grazing intensity or grazing abandonment have been proposed to improve oak regeneration in dehesas, but the effect of the recovery of non-continuous grazing practices such as transhumance has not been tested to date. We measured different indicators of holm oak regeneration and condition in dehesas under transhumant grazing and in dehesas under permanent grazing in southern Spain. Oak juveniles were remarkably less browsed and their canopies covered a much higher area in transhumant estates. As a consequence, the median density of saplings was more than four times higher in transhumant than in permanently-grazed estates. Although transhumant grazing is necessarily associated with a reduction in the stocking rate across the year, the timing of grazing was always included as a predictor in the best models to explain the condition and density of holm oak. Our results suggest that the lack of oak regeneration in dehesas can be caused not only by the increases in stocking rates, but also by the recent abandonment of traditional grazing practices like transhumance. We propose the recovery of seasonal grazing regimes based on transhumant pastoralism as a measure to improve the conservation status of dehesas.
Keywords: Agricultural intensification; Agroforestry; Browsing; Quercus ilex; Transhumance

Drove roads: Keystone structures that promote ant diversity in Mediterranean forest landscapes - Azcárate, Francisco M.; Seoane, Javier; Castro, Sara; Peco, Begoña (Acta Oecologica, 2013)
Abstract Drove roads are the traditional corridors used by pastoralists for seasonal movements of livestock (transhumance). They cover a considerable land area in Mediterranean countries and, although they are an obvious source of landscape diversity, their influence on the diversity and composition of animal assemblages has not been documented. Ant communities were studied on four active drove roads, two in forests (submediterranean and conifer) and two in open environments (croplands and rangelands). They were compared with the respective matrix communities and their contribution to local species richness was evaluated. The effects were heavily dependent on the open or closed nature of the matrix. In forest environments, drove roads increased ant species richness at the local scale, acting as clear keystone structures. Their species richness and functional diversity were highest on the fine scale, species composition was different, and a slight edge effect in the matrix was detected. In contrast, drove roads had little or even a negative effect in open environment locations. We conclude that drove roads have a high conservation value for ants in Mediterranean forest environments, in addition to their importance as reservoirs of plant biodiversity and generators of ecological goods and services.
Keywords: Ant assemblages; functional diversity; Grasslands; spatial heterogeneity; Transhumance

Drove roads as local biodiversity reservoirs: effects on landscape pattern and plant communities in a Mediterranean region - Azcárate, Francisco M.; Robleño, Irene; Seoane, Javier; Manzano, Pablo; Peco, Begoña (Applied Vegetation Science, 2012)
Question: What are the effects of traditional drove roads on landscape pattern and plant communities? Location: Madrid Autonomous Region, Central Spain. Methods: We selected four study localities in different landscape units. Within each locality, we selected eight sites and within each site, we established three 1-ha plots, each corresponding to one of three situations: drove road, adjacent matrix or distant matrix. The landscape pattern of each plot was characterized by the cover of the different patch types, the patch type richness ha 1 and the patch type evenness ha 1 . At one site per locality, we also recorded vegetation by randomly distributing twenty 20 cm 9 20 cm quadrats per plot. We characterized each quadrat by its species richness, plant species composition and plant functional composition. We also analysed species richness by constructing rarefaction curves for each plot. Results: In the localities situated in croplands, sub-mediterranean forests and coniferous forests, drove roads were found to be an important source of spatial heterogeneity and a reservoir for a large number of plant species. In contrast, drove roads did not differ from the matrix habitats in rangelands, suggesting that the processes shaping drove road vegetation are similar to the general processes that shape grazed systems. Drove roads did not imply a signiﬁcant increase in functional diversity. Our results were heavily scale-dependent: while drove roads provided heterogeneity at the local scale, they showed a remarkable similarity at the large scale. Conclusions: Drove roads act as authentic local biodiversity reservoirs, especially in environments with low grazing levels. At the same time, drove roads imply structural and functional continuity on a large scale, increasing potential connectivity at the regional level. We recommend the preservation of drove roads in a functional state, because of their beneﬁts to plant biodiversity conservation, and claim that these beneﬁts should be considered when designing livestock policies with different intensiﬁcation scenarios.
Keywords: extensive grazing; functional diversity; functional traits; landscape heterogeneity; Transhumance